Evaluation of a multi-species fodder surface area replacing a cereal crop in semi-arid areas of Algeria - Abbas K.; Madani T.; Laouar M.; M'Hammedi Bouzina M.; Abdelguerfi A. (Sustainable Mediterranean grasslands and their multi-functions, 2008)
Within the framework of the PERMED project and in order to reduce soil erosion and to improve the animal foddering system, a mixture of 9 varieties of annual and perennial species prepared by Fertiprado(r) were sown in November 2005 on a 1 ha surface area, replacing a cereal crop, on a farm located in the semi-arid area of Algeria, province of Sétif. 990 plants/m² emerged, of which 53% were sown, including 33% grasses. Vegetative biomass prior to grazing was 3.2 t DM/ha. Grasses account for 57% of them, legumes for 21% and the others for 21.5%. As an indication, the biomass produced by the sown mixture is twice as much as the quantity produced by a grazed fallow. The average biomass collected at the stage of cut in 8 enclosed cages corresponds to 3.8 t MS/ha. Its composition is 43% grasses, 22.5% legumes and 26.3% others.
12. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM Inter-regional Cooperative Research and Development Network on Pastures and Fodder Crop, 2008/04/09-12, Elvas (Portugal)